Chasing the wind : regulating air pollution in the common law state - Morag-Levine, Noga (Princeton University Press, 2003)
The Federal Clean Air Act of 1970 is widely seen as a revolutionary legal response to the failures of the earlier common law regime, which had governed air pollution in the United States for more than a century. Noga Morag-Levine challenges this view, highlighting striking continuities between the assumptions governing current air pollution regulation in the United States and the principles that had guided the earlier nuisance regime. Most importantly, this continuity is evident in the centrality of risk-based standards within contemporary American air pollution regulatory policy. Under the Eu.